Lower risk of ischemic stroke among patients with chronic kidney disease using chinese herbal medicine as add-on therapy: A real-world nationwide cohort study - Shen, Hsuan-Shu; Hsu, Chung-Yi; Yip, Hei-Tung; Lin, I-Hsin (Frontiers in Pharmacology, 2022)
Background The incidence of ischemic stroke (IS) is much higher among patients with chronic kidney disease (CKD) compared to the general population. Few studies have evaluated the association between the risk of IS and the use of Chinese herbal medicine (CHM) in patients with CKD. We aimed to investigate the risk of IS among patients with CKD using CHM as add-on therapy. Methods We conducted a retrospective cohort study based on Taiwan’s National Health Insurance Research Database to assess 21,641 patients with newly diagnosed CKD between 2003 and 2012. Patients were classified as either the CHM (n = 3,149) or the non-CHM group (n = 3,149) based on whether they used CHM after first diagnosis of CKD. We used the proportional subdistribution hazards model of Fine and Gray to examine the hazard ratio (HR) of IS in propensity-score matched samples at a ratio of 1:1 for two groups. Results The risk of IS was significantly reduced in the CHM group (adjusted HR [aHR]: 0.58, 95% confidence interval [CI]: 0.48–0.70) compared with the non-CHM group. Those who used CHM for >180 days had an even lower risk of IS than those in the non-CHM group (aHR: 0.51, 95% CI: 0.41–0.63). Additionally, frequently prescribed formulae, such as Ji-Sheng-Shen-Qi-Wan, Liu-Wei-Di-Huang-Wan, and Zhen-Wu-Tang were associated with a 30%–50% reduced risk of IS. Conclusion Our results suggest that patients with CKD who used CHM as add-on therapy had a lower hazard of IS than those in the non-CHM group, especially for patients taking CHM for >180 days. Further experimental studies are required to clarify the causal relationship.